Political and socio-economic convergence of religions in Nigeria: Positive views and interests - Orogun, Daniel (HTS teologiese studies, 2023)
Extensive review of academic writings on the convergence of religions (COR) in Nigeria shows that many online academic papers and related conversations gave more attention to its negative implications. Agreeably, Nigeria is the hotbed of religious crises in Africa. However, with the benefits of hindsight, filling the gap of insufficient capture of the positive impact of COR is considered in this exercise with three questions in view: (1) Where do religions meet? (2) Why do religions meet? (3) What are the positive implications of their convergence in Nigeria? Answers were adequately captured with examples, scenarios, case studies, historical evidence, and concomitant academic literature. Overall, this exercise projected three arguments. Firstly, it posited that commitment to religion is not at the heart of COR in Nigeria, rather, COR is premised on personal or group interests. Secondly, it argued that positive reflections on the COR can promote inter-religious tolerance, peace, and unity. Thirdly, it proposed that the COR has far-reaching positive implications socially, politically, and economically. Lastly, it made brief recommendations for improved co-existence and nation-building.Contribution: This article contributes to inter-religious dialogue in Africa as it focuses on the social, political and economic value of religion in Nigeria.